Acute impact of light at night and exogenous melatonin on subjective appetite and plasma leptin - Albreiki, Mohammed S.; Shamlan, Ghalia H.; BaHammam, Ahmed S.; Alruwaili, Nawaf W.; Middleton, Benita; Hampton, Shelagh M. (Frontiers in Nutrition, 2022)
This study investigates the possible effect of exogenous melatonin on appetite control by investigating plasma leptin and subjective appetite parameters. Nine healthy male participants (26 ± 1.3 years, BMI 24.8 ± 0.8 kg/m2 (mean ± SD) were recruited. The study was designed as a randomized three-way cross-over design; light (>500 lux) (LS), dark (<5 lux) + exogenous melatonin (DSC), and light (>500 lux) + exogenous melatonin (LSC), with an interval of at least 7 days between each session. Each session started at 18:00h and ended at 06:00h the following day. Participants were awake and in a semi-recumbent position during each clinical session. The meal times were individualized according to melatonin onset from 48h sequential urine collection, whereas melatonin intake was given 90 min before the evening meal. Subjective appetite parameters were collected at 30 min intervals during each session. Plasma leptin was collected at specific time points to analyze pre-prandial and postprandial leptin. Subjective hunger and desire to eat were reported higher in LS than DSC and LSC (P = 0.03, and P = 0.001). Plasma leptin showed a significant increase in LSC and DSC (p = 0.007). This study suggested a positive impact of exogenous melatonin on subjective appetite and plasma leptin.